Molecular dynamic simulation studies of hemidesmus indicus-derived oleanen-3-yl acetate in stat3 based tumor signaling - J Renukadevi; V S Karthikha; J Sam Helinto; D. Prena; Arockiya Rabin A (Journal of Applied Pharmaceutical Research, 2024)
Background: This study shows how oleanen-3-yl acetate, a plant substance found in Hemidesmus indicus, can be used as a medicine by looking at how it interacts with important signaling proteins in tumor inflammation. Methodology: Molecular docking and dynamics simulation analysis was carried out using PyRx and GROMACS to investigate the binding affinities and the interactions of oleanen-3-yl acetate with critical signaling protein receptors, including STAT3, NF-κB p105, and p53. Results: According to the docking studies, it has a strong binding energy of -8.1 kcal/mol for interacting with STAT3. This supports a strong downregulation of the STAT3-NF-κB signaling axis, a key factor in tumor inflammation. It sheds light on the conformational changes induced by Oleanen derivatives during binding, demonstrating its ability to destabilize the complex and enhance p53's apoptotic activity. Discussion: The RMSD values are maintained below at 2 Å throughout the simulation period, confirming the high structural stability of the ligand-protein complexes, while RMSF analysis is maintained at minimal fluctuation (<1.5 Å) involving key residues,  supporting the best ligand-protein interactions. The fluctuations in root mean square fluctuation (RMSF) and root mean square deviation (RMSD) values further elucidate their involvement in the initiation of apoptosis in cancer cells. Conclusion: It shows an effective way to find new drugs and gives useful information for the future development of therapeutic agents based on Hemidesmus indicus in tumor inflammation.  This research provides a robust technical foundation for further experimental validation and optimization in the drug development pipeline.